Osteomyelitis of Maxilla in Infantile With Periorbital Cellulitis: A Case Report. Issue 40 (October 2015) - Feng, Zhiqiang; Chen, Xufeng; Cao, Fengdi; Lai, Renfa; Lin, Qiang
Abstract : Abstract: Infantile osteomyelitis (IO) is an uncommon and life-threatening disease that can be misdiagnosed. Early diagnosis and treatment can reduce the incidence of sequel. In this case report, we present a 25-day-old male infant with apparent edema in the entire left periorbital region. Intraorally, the edema occurred in the mucosa of the upper left alveolar region, and 2 draining fistulas with exuded yellow-white pus were present in the left alveolar region. The patient received constant monitoring after admission, and was diagnosed as IO of the maxilla with periorbital cellulitis and sepsis. He also received incision and drainage and anti-inflammatory treatment. After discharge, the patient was followed up for 3 months by phone call, but no recurrence of symptoms was found. Infantile osteomyelitis is rare in clinic. This case report reminds us of the significance of IO and provides some implications on its diagnosis and treatment.